Comparison of influence on psychosocial factors of single and recurrent sexual abuse in childhood (Annals of Medical Research, 2021)
Aim: Sexual abuse in childhood, which is an important problem in the society, leads to many problems among the victims. This study aims to present the rate of being subject to recurrent sexual abuse and to find out the psychosocial characteristics of victims of recurrent sexual abuse. Materials and Methods: A total of 466 children were referred to the Ankara Child Follow-up Center during the first year. 35 children who had recurrent sexual abuse were compared with 36 first-time sexual abuse victims sociodemographic features, characteristics of sexual abuse and risk factors of sexual abuse.Results: 35 children who were victims of sexual abuse had been revictimized in the past. Children who had recurrent sexual abuse had statistically significantly higher rates of history of running away, school abstinence, broken family, problems in child-parent and parent-parent interrelations, alcohol use of family members, domestic violence and physical abuse than first-time sexual abuse victims. Conclusion: These findings support the need of immediate treatment both to the victims and their families to prevent recurrent sexual abuse to the child victims of sexual abuse. To achieve this, specialists working with children in various disciplines may collaborate with their colleagues in a multidisciplinary approach and they may provide proper treatments to the victims and their families to alleviate the risk factors. In hospital and school environments, victims of sexual abuse may be provided with the necessary skills of self-defense via psycho-education sessions, they may receive psychological support and their risky behaviors might be minimized while their social support mechanisms are being strengthened.
Keywords: Child; psychosocial factors; sexual abuse